2012
DOI: 10.1590/s0074-02762012000300006
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between genetic variability and the susceptibility of Biomphalaria alexandrina snails to Schistosoma mansoni infection

Abstract: In the present study, Biomphalaria snails collected from five Egyptian governorates (Giza, Fayoum, Kafr ElSheikh, Ismailia and Damietta)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…This prevalence rate is considerably higher than expected and has many indications. For example, it may indicate a recent human-water contact in spots with abundant occurrence of infected Biomphalaria alexandrina (Ehrenberg, 1831), the main intermediate host for S. mansoni in Egypt (lotFy et al 2005, MoHaMed et al 2012, abou el-naGa 2013. Thus, efforts should be directed to identifying such spots and to take appropriate measures.…”
Section: Introductionmentioning
confidence: 99%
“…This prevalence rate is considerably higher than expected and has many indications. For example, it may indicate a recent human-water contact in spots with abundant occurrence of infected Biomphalaria alexandrina (Ehrenberg, 1831), the main intermediate host for S. mansoni in Egypt (lotFy et al 2005, MoHaMed et al 2012, abou el-naGa 2013. Thus, efforts should be directed to identifying such spots and to take appropriate measures.…”
Section: Introductionmentioning
confidence: 99%
“…Biomphalaria which serves as an obligatory host for the larval stage, by which humans get infected. Among many identified species of Biomphalaria, Biomphalaria alexandrina is the intermediate host of S. mansoni in Egypt (Morgan et al, 2001;Lotfy, DeJong, Black, & Loker, 2005;Abou-El-Naga, El-Nassery, Allam, Shaat, & Mady, 2011;Mohamed, El-Din, Mohamed, & Habib, 2012).…”
mentioning
confidence: 99%
“…These primers might amplify very restricted areas of the genomes of B. glabrata and B. tenagophila specific for resistance or susceptibility, which are not present in B. alexandrina snails. Interestingly, one of these primers, the OPA-01 primer, resulted in high genetic variability between B. alexandrina strains from different provinces in Egypt using the RAPD-PCR technique [37]. The present study showed that with five out of the eight utilized primers, specific bands of different lengths were amplified in the resistant and susceptible phenotype snails.…”
Section: Discussionmentioning
confidence: 73%